Fatores preditivos de mortalidade em pacientes pediátricos com lesão renal aguda associada com sepse - Riyuzo, Marcia C. [UNESP]; Silveira, Liciana V. de A. [UNESP]; Macedo, Célia S. [UNESP]; Fioretto, José R. [UNESP] (Elsevier, 2017)
Objective To evaluate the prognosis factors of children with sepsis and acute kidney injury. Methods This was a retrospective study of children with sepsis and acute kidney injury that were admitted to the pediatric intensive care unit (PICU) of a tertiary hospital. A multivariate analysis was performed to compare risk factors for mortality. Results Seventy-seven children (47 males) were retrospectively studied, median age of 4 months. Mean length of hospital stay was 7.33 ± 0.16 days, 68.9% of patients received mechanical ventilation, 25.9% had oligo-anuria, and peritoneal dialysis was performed in 42.8%. The pRIFLE criteria were: injury (5.2%) and failure (94.8%), and the staging system criteria were: stage 1 (14.3%), stage 2 (29.9%), and stage 3 (55.8%). The mortality rate was 33.7%. In the multivariate analysis, the risk factors for mortality were PICU length of stay (OR = 0.615, SE = 0.1377, 95% CI = 0.469–0.805, p = 0.0004); invasive mechanical ventilation (OR = 14.599, SE = 1.1178, 95% CI = 1.673–133.7564, p = 0.0155); need for dialysis (OR = 9.714, SE = 0.8088, 95% CI = 1.990–47.410, p = 0.0049), and hypoalbuminemia (OR = 10.484, SE = 1.1147, 95% CI = 1.179–93.200, p = 0.035). Conclusions The risk factors for mortality in children with acute kidney injury were associated with sepsis severity.
Predictive factors of mortality in pediatric patients with acute renal injury associated with sepsis
Keywords: Acute kidney injury; Mortality; Predictive factors; Sepsis